AUDIT FEE AND TIME BUDGET PRESSURE ON AUDIT QUALITY (AN EMPIRICAL STUDY IN LOCAL CPA FIRMS IN JAKARTA, INDONESIA) - Judith Tagal Gallena Sinaga (Program Studi Magister Manajemen Universitas Advent Indonesia, 2022)
Audit quality is the aim of every business entity. A high quality audit gives a reliable information to all financial statements users. This study aims to examine the effect of audit fee (AF), time budget pressure (TBP) on audit quality (AQ) at several CPA firms in the city of Jakarta. Research questionnaire was used to gather research data which compose of nine (9) indicators and 30 research statements. There were four (4) Local CPA firms who participated to answer the questionnaire. Data collected were processed, interpreted and concluded. The results showed that audit fees and time budget pressure have significant effect on audit quality with a significance value of 0.014 while time budget pressure has a significant effect on audit quality with a significance value of 0.000, and audit fees and time budget pressure have a simultaneous effect on audit quality with a significance value of 0.000. This study implies that audit fee and time budget pressure pays a vital role to achieve a good and credible financial statements.